Evaluation of Fluoride Release in Chitosan-Modified Glass Ionomer Cements - Cruz Nishanthine; Revathi Miglani; Indira R; Saravanan Poorni; Manali Ramakrishnan Srinivasan; Ali Robaian; Nassreen Hassan Mohammad Albar; Susen Faisal Rajeh Alhaidary; Sultan Binalrimal; Abdullah Almalki; Thilla Sekar Vinothkumar; Harisha Dewan; et al. (Elsevier, 2022)
Objective: This study assessed the influence of chitosan nanoparticles on the fluoride-releasing ability of 4 glass ionomer cement (GIC) through an in vitro analysis. Methods: Four types of GIC (type II light cure universal restorative, type II universal restorative, GC Fuji VII, and type IX) were modified with nanochitosan particles; 10% chitosan was added to the glass ionomer liquid. Six specimens for each of the 4 groups were created, using expendable Teflon moulds. Discs of each type of GIC (n = 6) were immersed in deionised water at various time intervals. Electrodes selective for fluoride ions were employed to analyse the amount of released fluoride at 1, 7, 14, 21, and 28 days. Results: Chitosan-modified GICs showed greater fluoride release than conventional GICs at all time points. All samples showed an initial high release of fluoride that tapered off with time. The total amount of fluoride released increased from the 1st day to the 28th day on adding chitosan to all the 4 types of GIC. Amongst those, type IX high-strength posterior extra with chitosan released a considerably higher quantity of fluoride at all time intervals. Conclusions: In all the experimental groups, adding chitosan to the glass ionomer liquid had an accelerating effect on its fluoride-releasing property.